Freinet teacher's first movements in Extremedura: teachers, schools and papers - Antonio García Madrid (FahrenHouse, 2009)
There was in Spain an inicial «army of teachers» freinetians, a group of snipers commited to the renovation of the system of education which was born and grew in the shade of the Republic. To this army belonged the teachers' small squad of Extremadura, which took two schools of Las Hurdes as a surprising origin. From there it extended to Montijo -principal center of diffusion for the rest of the educational experiences in the region: Calamonte, Valencia de Alcantara, La Puebla del Maestre and, probably also, Arroyo del Puerco. Surprising is not only that the origin of such an educational innovation took place in a region like Las Hurdes, but also that it was proceeding almost at the same time as the huge movement in Catalonia and Aragon, and that it, most likely, was not affected by Almendros ́s influences. There are reasons to believe that the teacher Jose Vargas Gómez, the origin of everything, had early news from Freinet through the teachers from Torrijos and Camarena before arriving to Las Hurdes.